From scheme to praxis… – From a praxis to another praxis… – From praxis to competence… (Fiep Bulletin - online, 2014)
Associate Professor at Liège University (1953), Georges Bonaventure, one of the great Masters of French-speaking Belgian Physical Education thinking, has been, since the 60s, bringing his reflections about the role to be played by Physical Education in the fundamental modern teaching. His mission is well defined in one of the objectives of global education, that is: to stimulate children's disposition for physical activities related to health, to help them to reach an increasingly perfect command of their motor adaptability, to develop, in the long-run, the culture of sports practices, and to contribute to the improvement of school learning results through an interdisciplinary process. In this paper, the author describes the educator-teacher's purposes, and at the light of contemporary neuro-sciences knowledge, the following up process to motor skills at the educated adult stage: starting at the complete repertoire of schemes to be wakened, moving to the development, improvement and enriching process that will the child to attain a praxis set, that is, a set of voluntary actions conditioned by a specific functional objective that will be applied in life concrete skills. That education must respect the successive stages of the learning process, moving from the sensory-motor stage to the perceptive-motor stage and later to cognition. For that purpose, children should be provided with systematized life situations so that they can use all their potential power, and to do so in an orderly sequence of learning stages, avoiding skipping stages and making the great fundamental principles emerge for the control of movements. That should be so because knowledge does not assure competence is mastered, and it is necessary to fundament the learning of problem-situations, simplified but still rich of all the components and all the structures at which competence is aimed. So, a child will simultaneously learn to do and to be all that which only Physical Education allows each one's whole individuality to make true. Therefore, moving Physical Education to a peripheral status must be condemned. That misjudgment of its role happens whenever Physical Education is delegated to a specialist and because of that, other members of the educational community believe they are not committed to apply the educational virtues of motricity, and thus, they perpetuate the nefarious dichotomy tradition that has proven to be so damaging to the teaching quality and to children's interest.